First Report on the Artificial Cultivation Techniques of Buchwaldoboletus xylophilus (Boletales, Boletaceae, Buchwaldoboletus) in Southwest China - Tianwei Yang; Hongjun Mu; Liming Dai; Jing Liu; Xinjing Xu; Feng Gao; Yiwei Fang; Sipeng Jian; Mingxia He; Chunxia Zhang (Journal of Fungi)
Buchwaldoboletus xylophilus is an edible bolete species belonging to the family Boletaceae and the genus Buchwaldoboletus. It is found in tropical and subtropical regions, which are known for their rare wild resources. In this study, wild B. xylophilus was isolated and cultured, and its biological characteristics and artificial cultivation techniques were studied. The results show that the optimal carbon source, nitrogen source, and inorganic salt for the mycelium growth of B. xylophilus were maltose, ammonium tartrate, and magnesium sulfate, respectively. The most appropriate temperature was 28 °C, and the pH value was between 5 and 6. The most effective combination was determined via orthogonal experimentation, as follows: dextrose, ammonium nitrate, potassium dihydrogen phosphate, and 28 °C. The results of artificial cultivation in mushroom houses show that the mycelium of B. xylophilus was strong and grew well on the culture medium. The mycelial growth rate was 4.54 mm/d, and the fungus bags were filled about 50 days after inoculation. The primordia formed 9 to 14 days after covering with soil and the fruiting body matured in 6~8 days. The average yield of fresh mushrooms reached 131.07 ± 29.38 g/bag, and the average biological efficiency reached 28.48 ± 6.39%. In this study, artificial cultivation technology in respect of B. xylophilus in mushroom houses is reported for the first time. The fruiting bodies obtained through cultivation were identified using morphological and molecular biological methods. This technology offers benefits such as affordability, a brief cultivation cycle, substantial yields, and superior quality, making it ideal for industrial-scale and extensive cultivation.